Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.416
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions and Expectations of the Personally Controlled Electronic Health Record (PCEHR): A Case Study of Australias e-health Solution

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Researchers have shown that the patients using MHR have concerns to the legal, privacy and security issues of the system (Haddad et al, 2016;Muhammad and Wickramasinghe, 2017), but it is not clear about the views of other MHR users, such as clinicians and community health organizations, in the privacy and security aspects. Although two opt-out trials in Northern Queensland and the Nepean Blue Mountains areas (Department of Health, 2017) were conducted by the Government, they failed to capture the major issues of the opt-out model, as experts believed that "the concept is good" but the implementation was shocking (McCall, 2018).…”
Section: My Health Record and Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that the patients using MHR have concerns to the legal, privacy and security issues of the system (Haddad et al, 2016;Muhammad and Wickramasinghe, 2017), but it is not clear about the views of other MHR users, such as clinicians and community health organizations, in the privacy and security aspects. Although two opt-out trials in Northern Queensland and the Nepean Blue Mountains areas (Department of Health, 2017) were conducted by the Government, they failed to capture the major issues of the opt-out model, as experts believed that "the concept is good" but the implementation was shocking (McCall, 2018).…”
Section: My Health Record and Privacymentioning
confidence: 99%
“…These studies posit that privacy concerns are main barriers to prevent the adoption of PHRs. In Australia, people have similar concerns about unauthorized access, non-clinical use and data sharing, and they have adequate trust in the government agencies who run the MHR (Muhammad and Wickramasinghe, 2017). Notably, these concerns were measured when the MHR initiative was an opt-in model.…”
Section: Privacy Concerns In the Phr Contextmentioning
confidence: 99%
“…Akan tetapi tetap terdapat beberapa kekhawatiran mengenai perlambatan waktu pelayanan akibat harus menggunakan sistem daring MyHR. Dokter juga memiliki kekhawatiran akan berkurangnya independensi klinis akibat pengawasan yang lebih ketat dari institusi melalui sistem MyHR (Muhammed and Wickramasinghe, 2017). Kekhawatiran ini sepertinya cukup besar pada beberapa dokter hingga ada pengguna yang mengaku dihalangi untuk menjadi peserta MyHR oleh dokter keluarganya (Lupton, 2019).…”
Section: Tanggapan Penggunaunclassified